PRINSIP-PRINSIP KONTRAK KONSTRUKSI INDONESIA - Sugiarto Raharjo Japar, SRJ (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
The implementation of construction services must meet the principles of honesty and fairness, benefits, compatibility, balance, independency, openness, partnership and safety foremost in the interest of the community, nation and the state ( article 2 act no 18 years 1999 on construction services ).Then both users and providers services need to understand some of the stuff that fundamental i.e. the runway philosophical contractual relationship between providers of the construction services to the construction services and inspector construction services, the principle and legal norm the formation of legal construction contract, the principle and legal norm the implementation of legal construction contract . The legal research method in this journal uses a normative juridical research method with a statute approach that examines relevant laws and regulations and the conceptual approach that examines the theories and doctrines of experts in the field construction.